Ajuga orientalis L. Extract as a Green Corrosion Inhibitor of Aluminum in an Acidic Solution: An Experimental and DFT Study - Faten M. Abu Orabi; Sultan T. Abu-Orabi; Omaima A. Fodeh; Faisal K. Algethami; Abdel Monem M. Rawashdeh; Tareq T. Bataineh; Ghassab M. Al-Mazaideh; Mahmoud A. Al-Qudah (Metals, 2024)
The inhibitory effect of A. orientalis L. extract (AO) on aluminum corrosion in a 1.0 M HCl solution was investigated utilizing weight loss, electrochemical polarization, electrochemical impedance spectroscopy (EIS), and scanning electron microscopy (SEM). The results show that AO is a potent inhibitor in an acidic environment, and that the inhibition potency increases with concentration. Temperature investigations showed that, in an acidic medium, the efficiency decreased, increased, and then decreased as the temperature rose. Adsorption isotherms from Freundlich, Temkin, El Awady, and Redlich–Peterson (R-P) approximated the inhibitor’s adsorption properties. For the inhibitory behavior, a physical and chemical adsorption mechanism is proposed. The adsorption process’s thermodynamic parameters (Ea, ΔH*, and ΔS*) were determined and explained. The inhibitor, AO, was identified as a mixed-type (anodic and cathodic) inhibitor based on polarization studies. According to the SEM findings, the inhibitor partially covers the metal surface, providing it with a respectable level of protection. The weight loss, electrochemical polarization, EIS, scanning electron microscopy (SEM), and quantum chemical calculations show a strong agreement, indicating that the AO extract is a highly effective inhibitor of aluminum in an acidic solution.